THE SPRING OF THE NETWORKED NATIONS: SOCIAL MEDIA AND THE ARAB SPRING - Chorev, Harel (The Levantine Review, 2012)
This essay argues that social media played an important role in the Arab Spring and contributed to a change in the political culture of some of those countries that have gone through regime-change through 2011-2012. The article further posits that the contribution of social media was mainly instrumental, not causal, and that the main reasons behind the Arab Spring were problems generated by regional, local and global trends, affecting each country differently.